1976
DOI: 10.1177/001872677602901205
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Group Performance as Determinants of Egocentric Perceptions in Cooperative Groups

Abstract: Forty-eight male subjects who had previously completed Berger's selfacceptance (self-esteem) scale worked on problem-solving tasks in four person groups. After completion of the tasks, bogus feedback was provided which indicated that the group as a whole had done very well, very poorly, or average. No feedback was provided about the quality of individual performances. As predicted, perceptions of personal responsibility for the group's performance were found to be directly related to the quality of the bogus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 16 publications
2
21
1
Order By: Relevance
“…As in earlier studies (Schlenker & Miller, 1977a,b;Schlenker et al, 1976), group performance influenced subjects' perceptions of the accuracy of the measure of group performance, F( 1,84) =; 18.3, p < .001, and the amount of agreement existing within the group with regard to the decision problems, F( 1,84) = 12.9, p < .001. Subjects believed that the measure was more accurate and that more agreement had existed when the group succeeded rather than failed.…”
Section: Ancillary Measuressupporting
confidence: 66%
See 1 more Smart Citation
“…As in earlier studies (Schlenker & Miller, 1977a,b;Schlenker et al, 1976), group performance influenced subjects' perceptions of the accuracy of the measure of group performance, F( 1,84) =; 18.3, p < .001, and the amount of agreement existing within the group with regard to the decision problems, F( 1,84) = 12.9, p < .001. Subjects believed that the measure was more accurate and that more agreement had existed when the group succeeded rather than failed.…”
Section: Ancillary Measuressupporting
confidence: 66%
“…The female experimenter gave the subjects an instruction sheet which explained the events to follow, answered questions, and then distributed two decision problems for the subjects to consider individually. The problems were closely modeled after those used in previous studies (Schlenker & Miller, 1977b;Schlenker et al, 1976) and generally elicited a wide range of opinions from the subjects. One problem described the case of George, a kindly but incompetent employee who was doing his company more harm than good.…”
Section: Methodsmentioning
confidence: 99%
“…For example, in some Eastern cultures it is common to involve a third party as a way to indicate one's intention to resolve the conflict and preserve the other party's face (Schlenker, Soraci, & McCarthy, 1976). For example, in some Eastern cultures it is common to involve a third party as a way to indicate one's intention to resolve the conflict and preserve the other party's face (Schlenker, Soraci, & McCarthy, 1976).…”
Section: The Components Of Directness and Oppositional Intensitymentioning
confidence: 99%
“…More recent studies argue against the above conclusions. All of these included a neutral outcome condition in which subjects either did not receive information about their performance outcomes (Fitch, 1970;Larson, 1977) or received information that their performance was average (Kuiper, 1978;Lefcourt et al, 1975;Schlenker, 1975;Schlenker & MiUer, 1977a;Schlenker et al, 1976;Wolosin et al, 1973). The studies by Fitch (1970), Kuiper (1978) and the first experiment by Wolosin et al (1973) showed only self-enhancing effects; that is, in comparison to a neutral outcome condition, subjects made more internal attributions under success but did not make more external attributions under failure.…”
Section: Attributions Of Success and Failurementioning
confidence: 99%